The Impact of Store Atmosphere on Consumer Satisfaction in Purchasing Products - Indriani Wuri Puspitasari; Achmad Daengs GS; Enny Istanti; Rina Dewi (Global Economics: International Journal of Economic, Social and Development Sciences, 2025)
Business competition in the era of globalization has led various companies to compete in acquiring and maintaining their market share. This includes sectors such as trade, education, transportation, and others. This condition forces companies to develop appropriate strategies to achieve competitive advantage, ensuring they retain their market and win the competition. This research focuses on Sogo Surabaya, a shopping center visited by numerous consumers daily due to its strategic location in the city center, integrated with Tunjungan Plaza, and situated along a main road, making it easily accessible. Sogo Surabaya functions as a store providing various fashion-related needs, including formal attire such as suits and kebayas, as well as casual clothing for young people and teenagers, like t-shirts and jeans. The store atmosphere follows a typical shopping center design. Elements of the store atmosphere include interior design, product layout, air circulation, spatial arrangement, wall colors, room fragrance, furniture materials, and the products sold. The data used in this research is primary data obtained through questionnaires distributed to customers shopping at Sogo Surabaya.